MATM 9100 dual closure operators on a category and their applications - Jansen, Renier Stefan (University of the Free State, 2020)
Abstract not available
Keywords: Thesis (Ph.D. (Mathematics and Applied Mathematics))--University of the Free State, 2020; Category theory; Constant morphisms; Dual closure operators; Left and right constant subcategories; Cassidy Hebert Kelly dual closure operator; Adjunctions